Working time mismatch and job satisfaction - The role of employees' time autonomy and gender - Christian Grund; Katja Rebecca Tilkes (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Evidence shows that working time mismatch, i.e. the difference between actual and desired working hours, is negatively related to employees' job satisfaction. Using longitudinal data from the German Socio-Economic Panel, we examine the potential moderating effect of working time autonomy on this relation and we also consider the corresponding role of gender. First, individual fixed effects panel estimations reaffirm both the negative link of working hours mismatch and the positive relation of working time autonomy to employees' job satisfaction. Second, our results show a positive moderating relation of working time autonomy on the link between mismatch and job satisfaction. Third, our analyses hint at gender-specific differences: particularly women seem to benefit from the moderation role of working time autonomy.
Keywords: 330; working time mismatch; working hours discrepancies; job satisfaction; over-employment; Socio-Economic Panel; working time autonomy